Curvas de índice de sitio para Eucalyptus camaldulensis Dehnh en plantaciones puras del Ingenio San Antonio, Chinandega - Chávez Granera, C.A.; Duarte, E. Asesor (Managua (Nicaragua), 2001)
Sumario (Es)
Ilus.; 15 ref.
Tesis (Ing Agr)
Keywords: EUCALYPTUS CAMALDULENSIS; PLANTACION FORESTAL; DESARROLLO FORESTAL; PRODUCCION FORESTAL; NICARAGUA; INGENIO SAN ANTONIO; CHINANDEGA